The impact of China’s low-carbon city pilot policy on public health expenditure - Cui, Yanyin; Ren, Jie; Gao, Xupeng; Xia, Fang (Frontiers in Public Health, 2025)
ObjectiveIn driving a transition in environmental governance, China’s low-carbon city pilot (LCCP) policy has exerted a dichotomous impact on public health expenditure that is characterized by both a decline in relative proportion and expansion of absolute scale. Research to date is insufficient for understanding the transmission mechanisms and policy coordination pathways underlying this contradiction, which has hindered the sustainable realization of environmental health benefits. This study thus investigates the impact of China’s LCCP policy on public health expenditure and the underlying mechanisms involved.MethodsBased on panel data of 285 Chinese cities at the prefecture level and above from 2003 to 2019, a quasi-natural experiment was conducted using China’s LCCP policy. The time-varying difference-in-differences simulation method and hierarchical regression method were used to analyze the effect and mechanism of the LCCP policy on China’s public health expenditure.ResultsThe results demonstrate the inherently paradoxical nature of the effects of the LCCP policy on public health expenditure: although the LCCP policy produces a significant relative reduction in public health expenditure (β = −0.331, p < 0.001), it simultaneously produces a pronounced expansion in terms of absolute expenditure (β = 0.409, p < 0.001). These impacts are spatially heterogeneous across regions and exhibit supply–demand divergence in healthcare infrastructure readiness and environmental threshold effects that are contingent upon pollution severity gradients. Further analysis of the underlying mechanism reveals that public low-carbon behaviors serve as dual negative mediators in both expenditure dimensions, whereas household medical burdens exert a significant positive mediating effect on absolute expenditure but a statistically insignificant mediating effect on relative expenditure.ConclusionThis study reveals the complex synergistic mechanisms linking environmental governance to health investment allocation. The internal contradictory effects of the LCCP policy on public health expenditures must be resolved by striking a balance between environmental governance and health investment, implementing regional differentiation strategies, optimizing the structure of preventive expenditures, and guiding the public to collaborative participation. China’s environmental quality and public health should be promoted simultaneously.